Determinants of School Attainment of Boys and Girls in Turkey - Aysit Tansel (Yale University, Economic Growth Center, 1998)
This study investigates the determinants of school attainments of boys and girls in Turkey. Although high levels of enrollments have been achieved at the primary school level for both boys and girls in much of Turkey, substan- tial regional differences remain. In particular, in the Southeastern region, girls begin to drop out of school around the third grade. Only half of the primary school graduates register at the middle level. Thus, the purpose of this study is to examine the determinants of educational attainments at the primary, middle and high school levels. Attainments of boys and girls are examined separately so as to shed light on the causes for the significantly lower level of attainment for girls. Understanding the constraints causing the large gender gap in Turkish education and the covariates related to lower overall educational levels may be useful to policy makers and planners.
Keywords: I21; J16; 330; School attainments; gender; Turkey; Bildungsniveau; Bildungsverhalten; Allgemeinbildende Schule; Geschlecht; Türkei